Procesamiento del rechazo de banano para la producción de harina como proceso alternativo para alimentos de cerdos - Grefa Yumbo, Jofre Sergio (2019)
This project enters the design and construction of equipment such as the solar dryer and the artisan mill in order to elaborate flour of banana waste. The problematic situation of banana plantations and their waste was previously assessed during this project, which can be used as pig feed, the artisanal equipment established an alternative to use banana waste for flour production and taking into account the requirements established by the technical regulations of processed foods and food processing plants issued by MAGAP in conjunction with AGROCALIDAD. That one may concentrate this objective it starts drying the banana previously sliced, for which the solar dryer is used; once the optimum dehydration has been obtained, it is proceeded to grind with the built mill, thus determining the banana flour, the same one that was subjected to a physical-chemical study, obtaining the somewhat low nutritional characteristics; with this result, the nutritional content was improved by adding the wheat bran that allowed to recover the optimal nutritional percentages, resulting in: total humidity 12.07%, dry matter 87.93%, proteins 11.53%, fiber 2.09%, fat 1.25%, ash 3.89%, organic matter 96.11%.